Pengaruh Manajemen Kelas Teknik Diskusi Stix Terhadap Belajar Siswa Pada Mata Pelajaran Aqidah Akhlak Di Mts Nahdlatul Muslimin Undaan Kudus - Anas, Khoerul; Nirawati, Alvi (JPT : Jurnal Pendidikan Tematik, 2020)
The purpose of this research are (1) To know the influence between class management against learning student participation on Aqidah Akhlak lesson in MTs Nahdlatul Muslimin Undaan Kudus, (2) To know the influence between stix discussion technique against student learning participation on Aqidah Akhlak lesson in MTs Nahdlatul Muslimin Undaan Kudus, (3) To know the influence between class management by stix discussion technique against student learning participation on Aqidah Akhlak lesson in MTs Nahdlatul Muslimin Undaan Kudus. This research use methods : observation, questionnaire, and documentation. The result explain that 1) There is a significant influence between class management against student learning participation on Aqidah Akhlak lesson in MTs Nahdlatul Muslimin Undaan Kudus, there is 0,474 included in medium category, 2) There is a significant influence between stix discussion technique against student learning participation on Aqidah Akhlak lesson in MTs Nahdlatul Muslimin Undaan Kudus, there is 0,720 included in strong category, 3) There is a significant influence between class management by stix discussion technique against student learning participation on Aqidah Akhlak lesson in MTs Nahdlatul Muslimin Undaan Kudus, there is 0,726 included in strong category.